PS 08-69 INTRACRANIAL VESSEL STIFFNESS IN POST-REPAIR PATIENTS WITH AORTIC COARCTATION. (September 2016) - Howe, Peter; Wong, Rachel; Ahmad, Waheed; Spratt, Neil; Levi, Chris; Collins, Nicholas
Abstract : Objective: Coarctation of the aorta (CoA) is one of the most common congenital cardiovascular anomalies and is associated with reduced life expectancy due to sources of morbidity, including intracerebral aneurysm formation, despite improved postoperative outcomes. We hypothesised that patients with a history of aortic coarctation may have abnormalities of cerebral blood flow compared with controls. Design and Method: Thirteen adult patients (77% males, mean age of 36.1 ± 3.7 years), 12 of which had undergone previous surgical repair to relieve obstruction, and 13 age-gender matched controls (mean age 38.8 ± 3.9 years) underwent assessments of blood pressure, arterial compliance and cerebrovascular function. Transcranial Doppler ultrasound was used to assess basal mean blood flow velocity in the middle and posterior cerebral arteries (MCA and PCA respectively) and stiffness of cerebral vessels, as determined by pulsatility and resistive indices. Cerebrovascular responsiveness (CVR) to a 3-min hypercapnic challenge (95% O2/5% CO2) in the MCA was recorded the peak velocity achieved during hypercapnia expressed as a percent change from the basal velocity. Results: Both groups were normotensive. However, pulse pressure was 17% higher in the patient group (P = 0.013) compared with the controls despite similar systemic blood pressure and arterial compliance in both groups. In both the MCA and PCA, the patient group exhibited significantly increased stiffness of the intracranial vessels (16–30% greater pulsatility in the MCA and 16–37% greater in the PCA). Additionally, CVR to hypercapnia was 35% lower in the patient group. Conclusions: It appears that in normotensive repaired CoA patients, intracranial arteries are stiffer and cerebral vasodilator function is compromised. Further investigation is warranted to assess whether these abnormalities might predispose patients to stroke or cerebral aneurysm formation.